Association of beta‐blocker treatment with mortality following myocardial infarction in patients with chronic obstructive pulmonary disease and heart failure or left ventricular dysfunction: a propensity matched‐cohort analysis from the High‐Risk Myocardial Infarction Database Initiative. (24th October 2016) - Coiro, Stefano; Girerd, Nicolas; Rossignol, Patrick; Ferreira, João Pedro; Maggioni, Aldo; Pitt, Bertram; Tritto, Isabella; Ambrosio, Giuseppe; Dickstein, Kenneth; Zannad, Faiez
Abstract : Aims: To determine the influence of baseline beta‐blocker use on long‐term prognosis of myocardial infarction (MI) survivors complicated with heart failure (HF) or with left ventricular dysfunction and with history of chronic obstructive pulmonary disease (COPD). Methods and results: Among the 28 771 patients from the High‐Risk MI Database Initiative we identified 1573 patients with a baseline history of COPD. We evaluated the association between beta‐blocker use at baseline (822 with beta‐blocker and 751 without) on the rates of all‐cause and cardiovascular mortality. On univariable Cox analysis, beta‐blocker use was found to be associated with lower rates of both all‐cause [hazard ratio (HR) = 0.61, 95% confidence interval (CI) 0.51–0.75, P < 0.0001] and cardiovascular mortality (HR = 0.63, 95% CI 0.51–0.78, P < 0.0001). After extensive adjustment for confounding, including 24 baseline covariates, COPD patients still benefited from beta‐blocker usage (HR = 0.73, 95% CI 0.60–0.90, P = 0.002 for all‐cause mortality; HR = 0.77, 95% CI 0.61–0.97, P = 0.025 for cardiovascular mortality). Adjusting for propensity scores (PS) constructed from the 24 aforementioned baseline characteristics provided similar results. In a cohort of 561 pairs of patients taking or not taking beta‐blocker matched on PS using a 1:1 nearest‐neighbour matching method, patients treated with beta‐blocker experienced fewer all‐cause deaths (HR = 0.71, 95% CI 0.56–0.89, P = 0.003) and cardiovascular deaths (HR = 0.76, 95% CI 0.59–0.97, P = 0.032). Conclusions: In the specific setting of a well‐treated cohort of high‐risk MI survivors, beta‐blockers were associated with better outcomes in patients with COPD.